Gendered Impoliteness and Identity Negotiation in Teenage Discourse: A Socio-Pragmatic Analysis of Barely Lethal - Alfan Amin; Bejo Sutrisno (CV. Creative Tugu Pena, 2025)
This study investigates the gendered deployment of impoliteness strategies in adolescent discourse as portrayed in the action-comedy film Barely Lethal. Anchored in Culpeper’s (2011) impoliteness typology and informed by feminist and sociolinguistic theories of discourse and identity, the research adopts a socio-pragmatic lens to explore how teenage characters of different genders enact verbal aggression, negotiate social power, and construct identities. Using qualitative content analysis, the study analyzes 15 transcribed utterances across key scenes. Results indicate that negative impoliteness is the most frequently used strategy, particularly among female characters. Sarcasm, mock politeness, and bald-on-record expressions are also salient, with notable gendered differences in distribution and function. Female characters exhibit more strategic, relational, and performative use of impoliteness, while male characters rely predominantly on direct, hierarchical speech acts. These findings underscore how impoliteness functions as a gendered linguistic resource within mediated adolescent interaction. The study offers empirical and theoretical contributions to gendered discourse analysis, youth pragmatics, and media sociolinguistics.